Defining danger : American assassins and the new domestic terrorists - Clarke, James W., 1937- (Transaction Publishers, 2007)
"In Defining Danger, James W. Clarke explores the cultural and psychological linkages that define assassinations and a new era of domestic terrorism in America."--BOOK JACKET.